The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1063/1.5012554
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory study of interaction of magnetoplasma irregularities produced by several radio-frequency heating sources

Abstract: The dynamics of a group of narrow field-aligned plasma density irregularities is studied using the large-scale KROT plasma device. The chosen experimental conditions are similar to the conditions in the ionosphere of the Earth, where such irregularities develop under the impact of high-power, high-frequency radio waves. In our laboratory experiment, the irregularities are created by a set of rf antennas arranged in a row across the ambient magnetic field due to the heating of electrons and subsequent redistrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Perhaps, this is due to the fact that the active experiment was carried out in the late morning (normally, the daytime ducts were weaker than those in the nighttime using the HAARP and SURA facilities Frolov et al., 2016; Vartanyan et al., 2012), there was a small pump wave power, and the pump wave frequency was almost equal to the critical frequency f 0 F 2 . Note that the effects of the interaction of the irregularities were studied near to and far from the heating source in laboratory experiments on modeling ionospheric heating (Aidakina et al., 2018, 2018a). It was shown that near the heating sources, the irregularities had the form of a set of channels with reduced plasma density and a transient process with a positive density perturbation was observed at a large distance from the heating sources.…”
Section: Results Of the Joint Sura‐norsat‐1 Experimentsmentioning
confidence: 99%
“…Perhaps, this is due to the fact that the active experiment was carried out in the late morning (normally, the daytime ducts were weaker than those in the nighttime using the HAARP and SURA facilities Frolov et al., 2016; Vartanyan et al., 2012), there was a small pump wave power, and the pump wave frequency was almost equal to the critical frequency f 0 F 2 . Note that the effects of the interaction of the irregularities were studied near to and far from the heating source in laboratory experiments on modeling ionospheric heating (Aidakina et al., 2018, 2018a). It was shown that near the heating sources, the irregularities had the form of a set of channels with reduced plasma density and a transient process with a positive density perturbation was observed at a large distance from the heating sources.…”
Section: Results Of the Joint Sura‐norsat‐1 Experimentsmentioning
confidence: 99%
“…In so doing, the ambient plasma is involved in the eddy current excited in such a thermal unipolar diffusion regime, which leads to the propagation of disturbances beyond the beam of powerful radio waves. Over time, the depth and the length of the density depletion around the heating region increase; the density enhancement travels away from the heating source (Aidakina et al, ). The proportionality between the magnitude of the T e and N e disturbances observed in space as well as the current densities (taken into account the geometrical scales) is good agreement with the quantitative estimates from the laboratory modeling presented by Aidakina et al ().…”
Section: Interpretation Of the Observational Resultsmentioning
confidence: 99%
“…The possibility of the effects observed by SWARM was previously demonstrated in laboratory experiments. The laboratory modeling performed with KROT plasma facility under the experimental conditions similar to the conditions in the ionosphere, where the plasma irregularities develop under the impact of high‐power HF radio waves, has revealed redistribution of plasma accompanied by electric currents (Aidakina et al, , ; Kostrov et al, ; Starodubtsev et al, ). Because the heated electrons escape along the magnetic field lines, channels with reduced plasma density and enhanced N e above the depletion are formed.…”
Section: Interpretation Of the Observational Resultsmentioning
confidence: 99%
“…First of all, this interest is stimulated by the fact that a wide range of plasma density irregularities, which have the transverse dimensions from several meters to a few kilometers, can spontaneously or artificially be created in the ionosphere and the magnetosphere. For example, artificial field-aligned plasma structures are often observed in heating ionospheric [20,[36][37][38][39][40][41][42][43][44] and laboratory [2][3][4][5][45][46][47][48] experiments. Despite significant progress in the studies of scattering characteristics of density irregularities in a magnetoplasma [12][13][14][15]49], little is known about the features of resonance scattering from such plasma structures in the situation where the incident radiation is excited by antennas located near the scattering objects.…”
Section: Introductionmentioning
confidence: 99%